2009
DOI: 10.1055/s-0029-1215024
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection allows less-invasive curative resection for gastric tube cancer after esophagectomy – a case series

Abstract: Detection of early gastric tube cancers (GTCs) has increased with more detailed surveillance endoscopy using indigo carmine dye following esophagectomy. This retrospective study clarified the clinicopathological features and application of endoscopic submucosal dissection (ESD) for GTCs. Data collected for eight GTCs treated by ESD included clinical and pathological features and outcomes following ESD. Overall, eight GTCs were identified in seven (6.3 %) of 112 patients who underwent esophagectomy and gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…ESD offers advantages in terms of the shape and size of the resectable lesions compared with conventional EMR and has enabled successful en bloc resection of various cancers [2][3][4]. Several reports have indicated that a high en bloc resection rate was achieved by ESD in the remnant stomach, despite some technical difficulties [5][6][7][8][9]. Lesions located at anastomotic sites are expected to be much more difficult because there are severe fibrosis and staples from the previous surgery, and because there is the need for resection of duodenal or small intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…ESD offers advantages in terms of the shape and size of the resectable lesions compared with conventional EMR and has enabled successful en bloc resection of various cancers [2][3][4]. Several reports have indicated that a high en bloc resection rate was achieved by ESD in the remnant stomach, despite some technical difficulties [5][6][7][8][9]. Lesions located at anastomotic sites are expected to be much more difficult because there are severe fibrosis and staples from the previous surgery, and because there is the need for resection of duodenal or small intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, delayed perforations did not occur in any case. However, the possibility of delayed perforation should not be ignored in fibrotic areas that are subjected to excessive electrocautery effects [23]. In the future, additional large studies are required to demonstrate the influence of the tumor's involvement with the suture lines on the increased risk of perforation during ESD for GEN-RS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not surprising that mucosally based neoplastic lesions such as esophageal squamous cancers, adenocarcinomas associated with Barrett’s esophagus, and gastric cancers are the most common targets for this therapy in the upper gastrointestinal tract [24]. Less common usages would be for the removal of submucosal lesions such as leiomyomas or GIST [5].…”
Section: Indications For Proceduresmentioning
confidence: 99%